Childhood Degenerative Disorders and Adult Dementia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
An approach to the evaluation of dementia in adults related to pediatric metabolic and degenerative diseases is reviewed from the Department of Neurology, University Medical Center, Maywood, IL.